Designing Climate Action and Regulations for sustainaBility (DCARB): Framework and campus application. (1st July 2022) - Charles, Michael; Vattyam, Vivek; Bakshi, Bhavik R.
Abstract: With increased understanding of the impacts of climate change, institutions across the world are committing to achieve carbon neutrality and other emissions reduction targets. Within academia, the American College & University Presidents' Climate Commitment was created as a highly visible public contract with over 300 active signatories. Existing climate action planning tools rely on significant subjectivity and previously conducted project analysis. This work presents an optimization framework that develops a long-term planning tool tailored for use by academic institutions. Further, we highlight the potential for ecological solutions and land management as economically competitive actions for campuses. The presented tool, known as DCARB (Designing Climate Action and Regulations for sustainaBility), features an ability to quickly optimize multiple pathways towards carbon neutrality based on user-input and parameter variability. We showcase DCARB through an application for The Ohio State University to demonstrate the outputs of the tool based on current projects outlined in the institution's climate action plan. Additionally, parameter variability is analyzed to explore how solutions might change due to data uncertainty or application to other campuses. The results encourage urgent action as they can provide cheaper pathways towards neutrality, including immediate consideration of land-based actions. Additionally, applications of the tool highlight challenges for achieving neutrality such as a reliance on market-based offsets, future market volatility, proper carbon credit accounting, and planning for future social and behavioral actions.